Content and Language Integrated Learning (CLIL) in European Higher Education - Katarzyna Papaja (Ignatianum University Press, 2023)
The following article discusses Content and Language Integrated Learning (CLIL) in European higher education, which has become popular in recent years due to the status of English as a foreign language. Firstly, the difference between CLIL and English Medium Instruction (EMI) is explained, then CLIL modules in higher education are presented. Furthermore, CLIL special pedagogy in higher education is described. The subsequent section is devoted to the benefits and challenges of CLIL in higher education as listed in the literature; finally, insight into research on language in the CLIL higher education context is addressed. The data presented in the article is based on an in-depth literature review and research conducted in higher education institutions in Europe. The findings show that even though CLIL has become a popular approach in higher education in recent years, adapting this concept has been a great challenge due to the very little preparation, proper methodological training and complex linguistic learning situations.